Research Procedure: An Introduction - Bist, Resham Bahadur (Journal of NELTA Surkhet, 2015)
Research is common phenomenon to investigate the resolution of existing problems and generate the new dimension of knowledge in all sectors. It aims to contribute to the advancement of knowledge and wisdom which is undertaken with its certain system and procedures. Regarding the issue of research, this article aims to explain briefly what research is, its significance, and its purposes. It then mentions about the types of research and its methods, processes, and qualities briefly. Journal of NELTA Surkhet Vol.4 2014: 34-40